'Going off the Map': Dependent Arising in the Nettippakaraṇa. (31st December 2019) - Jones, Dhivan Thomas
Abstract : The early Buddhist exegetical text, the Nettippakaraṇa, apparently uniquely, describes the stages of the path as 'transcendental dependent arising' (lokuttara paṭicca-samuppāda), in contrast with the twelve nidānas, called 'worldly dependent arising' (lokiya paṭicca-samuppāda). A close reading of the Nettippakaraṇain relation to another, related, exegetical text, the Peṭakopadesa, reveals that the latter interprets the same stages of the path in a different way. More broadly, while the Peṭakopadesa takes paṭicca-samuppādato refer only to the twelve nidānas, the Nettippakaraṇa's exegetical strategy takes paṭicca-samuppādato refer to an over-arching principle of conditionality, both 'worldly' and 'transcendental'. This exegesis has proved popular with modern western Buddhist exegetes.